Gender-Specific Peculiarities of Motor Preparedness of Children Aged 6-10 - О. В. Іващенко (OVS LLC, 2017)
The objective is to determine the gender-specific peculiarities of motor preparedness of children aged 6-10.  Materials and methods: the participants in the study were girls aged 6 (n = 36), aged 7 (n = 48), aged 8 (n = 57), aged 9 (n = 38), aged 10 (n = 46); boys aged 6 (n = 48), aged 7 (n = 45), aged 8 (n = 60), aged 9 (n = 47), aged 10 (n = 40). To achieve the tasks set, the study relied on the following research methods: analysis of scientific literature, pedagogical testing and methods of mathematical statistics of research data reduction. The study used discriminant analysis as the modeling method. Results: the classification results of motor preparedness of girls and boys aged 6-10 indicate that the study has correctly classified 81.9-100% of the initial observations. The graphic material demonstrates the density of objects within each class and a clear distinction between the classes. This allows to maintain that there is a significant difference between girls and boys aged 6-10 in their motor preparedness. Conclusions. The girls aged 6-10 show the best results in movement coordination related to combinations of movements of arms and legs, as well as flexibility. The girls aged 10 show the best results in test No. 10 "300-m Race". The boys aged 6-10, unlike the girls, show the best results in the development of general coordination of movements, strength, speed strength, strength and general endurance. It is possible to argue with a high level of reliability that by their classification characteristics girls and boys belong to different classes, and significantly differ in motor preparedness.